Public governance students' opinion about the role of the government in environmental responsibility - Berényi László; Deutsch Nikolett; 29th International Symposium on Analytical and Environmental Problems Szeged 2023. november 13-14. (University of Szeged Szeged, 2023)
Solving environmental problems goes beyond the scope of natural and engineering sciences. Social issues must be considered since people are the ultimate beneficiaries or sufferers of the related decisions. Due to the complexity of the problems and the required toolset of the solution, social aspects cover several questions. The role of the government is remarkable in financial, policy-making, and other aspects. The study deals with the individual judgment on the role of the government. The scope is limited to Hungarian higher education students as a pilot study. The results show competing patterns that can contribute to a better understanding of personal opinions.
Keywords: Társadalomtudományok; Politikatudomány